PERAN PEMERINTAH DAERAH KABUPATEN KAMPAR DALAM MENSOSIALISASIKAN PERATURAN DAERAH NOMOR 7 TAHUN 2012 TENTANG RETRIBUSI JASA UMUM (STUDI KASUS DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR) - Helmi Hardiansyah; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
ROLE OF GOVERNMENT REGULATION Kampar district in socialized LOCAL NUMBER 7 IN 2012 ON PUBLIC SERVICES LEVY (CASE STUDY IN CITY DISTRICT DISTRICT Bangkinang KAMPAR). And the purpose of this study was to analyze the role of Knowing and Kampar regency administration in Socializing Regional Regulation No. 7 of 2012 on Public service levies and Knowing and analyzing the factors causing maximal dissemination Regional Regulation No. 7 of 2012 on the General Services Levy. This study uses qualitative research methods to include an assessment of descriptive data f. By using the key resource of information. Based on the research that has been conducted based on the concept and theory of Hovland. Researchers conclude Whereas the Public Relations Kampar regency administration in accordance with the duties and functions implementing policy publications, events, actions and programs of government. The role of PR in general lead to management control efforts, especially with regard to organizational communication. Usually made concerning the role of the formulation of ideas or good ideas that can be presented to the overall subsystem within the organization with regard to public attitudes, feelings public, the public needs, and aspirations. Questioning then Bylaw No socialization. 7 of 2012 on the General Services Retibusi in Kampar district, especially in the District Bangkinang City, Public Relations Department had socialized in coordination with the relevant agencies. In addition, the Public Relations Department also utilizes mass media and information boards in order to convey a general policy that charges for services.Keyword : Local Government, Socialization, Services General Levy